If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lnx + ln(x + -5) = 0 Reorder the terms: lnx + ln(-5 + x) = 0 lnx + (-5 * ln + x * ln) = 0 lnx + (-5ln + lnx) = 0 Reorder the terms: -5ln + lnx + lnx = 0 Combine like terms: lnx + lnx = 2lnx -5ln + 2lnx = 0 Solving -5ln + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-5 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5 + 2x)' equal to zero and attempt to solve: Simplifying -5 + 2x = 0 Solving -5 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 0 + 5 2x = 0 + 5 Combine like terms: 0 + 5 = 5 2x = 5 Add '-2x' to each side of the equation. 2x + -2x = 5 + -2x Combine like terms: 2x + -2x = 0 0 = 5 + -2x Simplifying 0 = 5 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x-17=-11 | | c+z-x=h | | 4/7t=2 | | 12t-36=60 | | 2(3x+2)=3(x-4) | | 56=23w | | 8(w+2)=72 | | 12.5=t | | 5/8x8/3 | | h-(c+v)=3 | | 5b-11=9b+29 | | xsquare-5x+6=0 | | 8-2/9x=1/3 | | 3((7(x-2)+4)-(2(2x-5)+6))= | | u=h-(c+v) | | 1-4/7 | | 40x-60=40x-60 | | 6(x+2)=5(x-2)+x | | 3x/4+4=10 | | (4u-2)(1+u)=0 | | 3x+5+2x-15=180 | | 1-7/15 | | -42x+-30=-7+-42x | | 16+3x-8x=6x+5x | | 6x-48=3x-15 | | 1/25x=2 | | us+uv=t | | (x-4)(3x+7)= | | 4-2(x+4)=6x-5(-x+3) | | 14x-21=4x | | x-(c+w)=h | | Y=-xsquared |